2020
DOI: 10.1002/ajp.23115
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of macaques as seed dispersers

Abstract: Seed dispersal is an ecological process crucial for forest regeneration and recruitment.To date, most studies on frugivore seed dispersal have used the seed dispersal effectiveness framework and have documented seed-handling mechanisms, dispersal distances and the effect of seed handling on germination. In contrast, there has been no exploration of "disperser reliability" which is essential to determine if a frugivore is an effective disperser only in particular regions/years/seasons or across a range of spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Our results are in agreement with the finding that seeds with MCD > 3 mm were predated [ 44 ]. Although large seeds were damaged at a high rate in our study, the encrustation of berries from genuine fruits may have a positive influence on intact seed ingestion by monkeys, and previous research has identified the genus Macaca as a reliable seed disperser [ 45 ]. Our findings could point to the possibility of Tibetan macaques dispersing seeds with an MCD of less than 3 mm.…”
Section: Discussionmentioning
confidence: 72%
“…Our results are in agreement with the finding that seeds with MCD > 3 mm were predated [ 44 ]. Although large seeds were damaged at a high rate in our study, the encrustation of berries from genuine fruits may have a positive influence on intact seed ingestion by monkeys, and previous research has identified the genus Macaca as a reliable seed disperser [ 45 ]. Our findings could point to the possibility of Tibetan macaques dispersing seeds with an MCD of less than 3 mm.…”
Section: Discussionmentioning
confidence: 72%
“…(Preference indices) = ratio of number of feeding scans for the consumed species to the total number of feeding scans/ratio of number of stems for the consumed species of the total number of stems into the botanical plots. Preference indices >1 indicate a preference for a fruit family [50]; -= no data; Processing methods: W = swallow, S = spit out. Grey shaded rows present the species used for the simulations of a species seed shadow using the mechanistic Model of Seed Tranfert (MOST).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we estimated seed shadow of a subset of three trees and one liana species, with medium and large seeds, to illustrate species specific variability (i.e., seasonal distribution and availability, plant traits, seed treatments). We selected these four plant species among the most consumed within macaques' diet or with the highest preference indices (based on the species relative consumption over the species relative availability, following Sengupta et al [50]) and either abundant or rare across macaques' home range.…”
Section: Ranging Movement Patterns and Seasonalitymentioning
confidence: 99%
“…While the term stomatochory was used as far back as the 1980s (van der Pijl, 1982), it has rarely been used in the seed dispersal literature until the last decade when it was applied to seed dispersal by parrots (Blanco et al., 2015; Tella et al., 2015). Despite an increasing number of studies documenting stomatochoric dispersal (Aziz et al., 2021; Baños‐Villalba et al., 2017; Blanco et al., 2019; McConkey & Brockelman, 2011; Sengupta et al., 2020), these studies remain largely species‐focused (rather than incorporated in community studies) and stomatochory is rarely considered a legitimate dispersal mode in comparison to endozoochory.…”
Section: Introductionmentioning
confidence: 99%
“…However, many seed disperser communities harbour abundant populations of non‐endozoochoric dispersers as well, who also consume fruits for the pulp, or even the seeds. Individually, these animals might not always disperse seeds as often and as far, but they can be frequent dispersers of viable seeds (Baños‐Villalba et al., 2017; Gómez et al., 2019; Ong et al., 2022; Sengupta et al., 2020). Furthermore, germination tests often show that the removal of pulp can have a stronger positive effect than seed scarification so that non‐endozoochoric dispersers can also enhance seed germination (Fedriani et al., 2012).…”
Section: Introductionmentioning
confidence: 99%